Method for preparing composite adhesive material by using waste cured microparticles and composite adhesive material

By mixing waste solidified microparticles with polyvinyl acetate emulsion to prepare composite adhesive materials, the problem of waste UV paint powder being unable to be effectively recycled is solved, the solid content and glue performance of the material are improved, and environmental pollution and production costs are reduced.

CN119614028APending Publication Date: 2025-03-14SUOFEIYA HOME COLLECTION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411935858.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art has failed to effectively recycle and reuse waste UV paint powder (waste cured microparticles), resulting in environmental pollution and high production costs.

Method used

The composite adhesive material is prepared by mixing 8%-20% of the waste cured microparticles with 80%-92% of the polyvinyl acetate emulsion and undergoing physical blending and modification.

Benefits of technology

It improves the solid content and glue performance of composite adhesive materials, effectively recycles waste solidified microparticles, and reduces environmental pollution and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614028A_ABST
    Figure CN119614028A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of recycling of waste UV coatings, in particular to a method for preparing a composite adhesive material by using waste cured microparticles and the composite adhesive material. The method for preparing the composite adhesive material by using the waste cured microparticles comprises the following steps: mixing 8-20% by mass of waste cured microparticles and 80-92% by mass of polyvinyl acetate emulsion, and uniformly stirring to obtain the composite adhesive material. Waste cured microparticles obtained after UV coating polishing and polyvinyl acetate emulsion are subjected to physical blending modification, the waste cured microparticles can replace inorganic filler added in a polyvinyl acetate adhesive, a large number of waste cured microparticles generated in coating industry processing are effectively recycled, and pollution of solid waste to the environment is reduced; the production cost of an enterprise is reduced; compared with the conventional polyvinyl acetate adhesive, the polyvinyl acetate adhesive has the advantages that the solid content and the bonding performance are improved to a certain extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of recycling waste UV coatings, and in particular to a method for preparing a composite adhesive material by utilizing waste solidified microparticles and the composite adhesive material. Background Art

[0002] The main components of UV coatings are thermosetting resins such as epoxy resin, acrylic resin, polyurethane resin, and unsaturated polyester resin. UV coatings have been widely used in the coating industry because they do not contain volatile organic compounds and have strong adhesion.

[0003] At present, in the process of using UV coating, after the UV coating is applied to the surface of the product by roller coating, spraying, etc., there is usually a polishing process to ensure that the surface of the product becomes smoother. This polishing process will produce a lot of waste UV paint powder, that is, waste solidified microparticles. Now most companies use large-scale central dust removal systems to first collect the waste solidified microparticles, and then carry out industrial treatment on a regular basis, and do not make use of them.

[0004] However, the waste solidified microparticles produced by sanding after UV coating is a non-degradable solid waste. When burned, it will produce toxic gases, which greatly pollute the environment. The current method for dealing with waste solidified microparticles is mainly deep pit burial, which has a high cost. At the same time, the storage requirements of waste solidified microparticles are also high. This is mainly because the waste solidified microparticles are photocured by UV ultraviolet high-energy rays, which can theoretically achieve 100% curing, but there are factors such as photoinitiators and light energy attenuation. The UV paint film may not be fully cured. After the light-cured UV coating is sanded with 400#-600#, it is within the combustible explosion range of solid dust due to its small size, so the storage conditions are stricter. Summary of the invention

[0005] The main purpose of the present invention is to provide a method for preparing a composite adhesive material using waste solidified microparticles and the composite adhesive material, aiming to improve the technical problem of not recycling and reusing waste UV paint powder (waste solidified microparticles) in the prior art.

[0006] To achieve the above object, the present invention provides a method for preparing a composite adhesive material using waste solidified microparticles, comprising the following steps: mixing 8%-20% of waste solidified microparticles with 80%-92% of polyvinyl acetate emulsion by mass percentage, and stirring to obtain a composite adhesive material;

[0007] The waste solidified micro-particles are waste particles remaining after the UV coating is polished.

[0008] Preferably, the waste solidified microparticles are sieved before mixing, and the particle size of the waste solidified microparticles after sieving is ≤250 μm.

[0009] Preferably, the waste solidified microparticles include waste solidified microparticles of epoxy resin, waste solidified microparticles of polyurethane resin and waste solidified microparticles of acrylic resin.

[0010] Preferably, the mass ratio of the epoxy resin waste solidified microparticles, the polyurethane resin waste solidified microparticles and the acrylic resin waste solidified microparticles is 2:1:2.5.

[0011] Preferably, by mass percentage, 12%-14% of the waste solidified microparticles are mixed with 86%-88% of the polyvinyl acetate emulsion and stirred evenly to obtain the composite adhesive material.

[0012] Preferably, the viscosity of the polyvinyl acetate emulsion is 9000-11000 mPa·S, and the pH value is 5-6.

[0013] Preferably, the molecular weight of the waste solidified microparticles is 15,000-25,000.

[0014] Preferably, the stirring speed is 200-300 r / min and the stirring time is 10-15 min.

[0015] In addition, the present invention also provides a composite adhesive material, which is prepared by any of the above-mentioned methods for preparing a composite adhesive material using waste solidified microparticles.

[0016] Preferably, at room temperature, the curing time of the composite adhesive material coated on the substrate is 1-2 hours, and the substrate comprises a wood material.

[0017] Compared with the prior art, the method for preparing a composite adhesive material using waste solidified microparticles and the composite adhesive material of the present invention have the following beneficial effects:

[0018] In this scheme, the waste solidified microparticles after UV coating polishing are physically blended and modified with polyvinyl acetate emulsion. The solid content and bonding performance of the obtained composite adhesive material are improved to a certain extent compared with conventional polyvinyl acetate adhesives; the waste solidified microparticles can replace the inorganic fillers added to polyvinyl acetate adhesives, which can effectively recycle a large amount of waste solidified microparticles generated in the coating industry processing, reduce the pollution of solid waste to the environment, and reduce the production costs of enterprises; it can also help polyvinyl acetate adhesive material manufacturers reduce the use of inorganic additives and improve product performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying any creative work.

[0020] Figure 1 It is the structural formula of polyvinyl acetate in this scheme.

[0021] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0024] A method for preparing a composite adhesive material using waste solidified microparticles comprises the following steps: by mass percentage, 8%-20% of waste solidified microparticles are mixed with 80%-92% of polyvinyl acetate emulsion, and stirred evenly to obtain a composite adhesive material; the waste solidified microparticles are waste particles remaining after UV coating is polished.

[0025] This solution innovatively proposes to physically blend and modify the discarded solidified microparticles after UV coating polishing with polyvinyl acetate emulsion (PVAc). The solid content and bonding performance of the obtained composite adhesive material are improved to a certain extent compared with conventional polyvinyl acetate adhesives. When the polyvinyl acetate emulsion is cured, the discarded solidified microparticles can be filled in its three-dimensional network polymer structure to form a lattice-like structure, thereby improving the bonding strength. Based on the principle of physical blending modification, the present invention adds the discarded solidified microparticles after UV coating polishing to the polyvinyl acetate emulsion and fully stirs them so that they fully enter the polymer chain at the microscopic level and play a supporting role in the formed chain links. The supporting role here refers to maintaining its structure by connecting different parts of the polyvinyl acetate emulsion polymer chain, which is mainly achieved through physical crosslinking (through intermolecular forces such as van der Waals forces or hydrogen bond formation). These crosslinks can provide additional stability and effectively fix the shape and structure of the polymer chain. For the long polymer chains of the polyvinyl acetate emulsion, self-crosslinking (such as Figure 1 The structure shown in the figure, -C=O easily reacts with the adjacent -H) and causes changes in the mechanical properties of the material, such as the strength and toughness may be reduced. This is because the structure formed after cross-linking will limit the mobility of the polymer chain, thereby reducing the deformability and ductility of the material; it also prevents the molding process from becoming more complicated due to self-crosslinking of the polymer. For example, during the processing, due to the self-crosslinking reaction, the polymer material will become too viscous and difficult to flow, which will increase the difficulty of the molding process and increase the production cost.

[0026] This scheme uses polyvinyl acetate emulsion as the main component, mainly because the bonding mechanism of polyvinyl acetate emulsion belongs to the combined action of active hydroxyl reaction type and physical glue nail type. Since the surface of wood and wood-containing composite materials has more pores, it is easier for polyvinyl acetate emulsion to infiltrate into the pores of the substrate to form a physical glue nail effect, which can reduce the generation of weak interface layer to a large extent, especially in the bonding of porous materials such as wood and wood composite materials. Based on this bonding mechanism, polyvinyl acetate adhesive materials are required to have a higher solid content.

[0027] The solid content of polyvinyl acetate emulsion can be increased by adding waste solidified microparticles. The waste solidified microparticles also have the advantages of high whiteness, strong hiding power, good dispersibility in the adhesive (based on the organic properties of the waste solidified microparticles, they are more likely to form hydrogen bonds with polar groups in polyvinyl acetate emulsion and are better dispersed in the polyvinyl acetate emulsion), good heat resistance and light resistance. The waste solidified microparticles after UV coating polishing have been cured by high-energy rays (high-energy ultraviolet light), and their physical and chemical properties are relatively stable. They can replace the inorganic fillers added to polyvinyl acetate adhesives, which can effectively recycle a large amount of waste solidified microparticles generated in the coating industry, reduce the pollution of solid waste to the environment, and reduce the production costs of enterprises; they can also help polyvinyl acetate adhesive material manufacturers reduce the use of inorganic additives and improve product performance.

[0028] The method for preparing a composite adhesive material using waste solidified microparticles of the present invention comprises the following specific preparation steps:

[0029] S1. Collect the waste solidified microparticles remaining after the UV coating on the door panel is polished through the central dust removal system; wherein, the specific components of the UV coating / paint generally include, by weight: 45-65 parts of photocurable resin (epoxy acrylate, polyurethane acrylate, polyester acrylate, polyether acrylate, amino acrylate, acrylate and other acrylates), 2-6 parts of photoinitiator, and additives (0.2-0.4 parts of defoamer, 0.2-0.3 parts of dispersant, 0.5-2 parts of leveling agent, and 30-50 parts of solvent); in the raw materials of the above-mentioned UV coating, the amount of photoinitiator added should not be greater than 6 parts, otherwise it is easy to cause incomplete curing or partial curing, which will reduce the quality of the waste solidified microparticles, such as increased surface viscosity, and will also shorten the effective use time of the prepared composite adhesive material, and weaken the other properties;

[0030] S2. The collected waste solidified microparticles are sieved to remove impurities for later use;

[0031] S3. Add the sieved waste solidified microparticles into 80%-92% polyvinyl acetate emulsion at a weight ratio of 8%-20% and stir until evenly mixed to obtain a composite adhesive material sample, which has no stratification after testing.

[0032] As the amount of waste solidified microparticles added to the polyvinyl acetate emulsion increases, the drying time of the composite adhesive material applied to the substrate will also be extended. If the amount of waste solidified microparticles added is greater than 20%, the composite adhesive material will take more than 24 hours to fully cure. 2. Polyvinyl acetate emulsion has good compatibility with solidified microparticles, and film stratification is not likely to occur.

[0033] Furthermore, the waste solidified microparticles are sieved before mixing, and the particle size of the waste solidified microparticles after sieving is ≤250 μm. When the particle size of the waste solidified microparticles is below 250 μm, the dispersion effect in the polyvinyl acetate emulsion is better, wherein the minimum particle size of the waste solidified microparticles is 20 μm.

[0034] Most preferably, the waste solidified microparticles with a particle size of ≤50um account for 20%, the particle size of 50-100um accounts for 30%, and the particle size of 200-250um accounts for 50%. At this time, the waste solidified microparticles of different particle sizes can be better filled in the three-dimensional network polymer structure of the polyvinyl acetate emulsion, and the performance of the composite adhesive material can be greatly improved.

[0035] Furthermore, the waste solidified microparticles include waste solidified microparticles of epoxy resin, waste solidified microparticles of polyurethane resin and waste solidified microparticles of acrylic resin, and the mass ratio of the three when mixed is 1.5-2:1:2-3.

[0036] The main component of UV coating / waste solidified microparticles is resin, and after solidification, resin also plays a major role. Waste solidified microparticles can be composed of one type of resin, or a mixture of multiple different resins can be used. When only one type of resin is used, the composite adhesive material obtained by blending polyurethane resin waste solidified microparticles formed by UV coatings mainly containing polyurethane resins and polyvinyl acetate emulsions has better performance. When multiple resins are used for mixing, epoxy resin waste solidified microparticles (formed by UV coatings mainly containing epoxy resins), polyurethane resin waste solidified microparticles (formed by UV coatings containing polyurethane resins) and acrylic resin waste solidified microparticles (formed by UV coatings containing acrylic resins) are mixed and then stirred evenly with polyvinyl acetate emulsions to obtain a composite adhesive material with better performance.

[0037] Furthermore, the mass ratio of the epoxy resin waste solidified microparticles, the polyurethane resin waste solidified microparticles and the acrylic resin waste solidified microparticles is 2:1:2.5.

[0038] In this embodiment, the content of waste solidified microparticles of acrylic resin has the greatest influence on the bonding strength of the composite adhesive material, followed by waste solidified microparticles of polyurethane resin. When waste solidified microparticles of epoxy resin, waste solidified microparticles of polyurethane resin and waste solidified microparticles of acrylic resin are mixed, there is an optimal mixing ratio, that is, the mass ratio is 2:1:2.5, and the bonding performance is optimal. Otherwise, the solid content of polyvinyl acetate emulsion is too large, which has a certain influence on the applicable period of the composite adhesive material (with the increase of solid content, the drying time of coating will be shortened); at the same time, the dispersibility of waste solidified microparticles in polyvinyl acetate emulsion will decrease, resulting in uneven dispersion, thereby affecting the wettability of the composite adhesive material on the surface of the substrate, and then affecting the bonding performance.

[0039] Furthermore, by mass percentage, 10%-12% of the waste solidified microparticles are mixed with 82%-90% of the polyvinyl acetate emulsion and stirred evenly to obtain a composite adhesive material. When the total amount of waste solidified microparticles added is about 10%-12%, the bonding performance of the obtained composite adhesive material is optimal.

[0040] Furthermore, the viscosity of the polyvinyl acetate emulsion is 9000-11000m Pa·S, and the pH value is 5-8. The viscosity of the polyvinyl acetate emulsion is adjusted to 9000-11000m Pa·S, and then the waste solidified microparticles are added so that the waste solidified microparticles can be better dispersed in the polyvinyl acetate emulsion; the pH value is adjusted to 5-8, so that the performance of the prepared composite adhesive material is better.

[0041] In summary, the waste solidified microparticles are directly generated by sanding with a sanding machine. Since the base and topcoat resin components of UV coatings are different, it is difficult to use them directly. The present invention simultaneously selects multiple parameters such as the particle size, addition amount, type of the waste solidified microparticles and the type of adhesive compounded therewith (polyvinyl acetate emulsion) to ensure that the obtained composite adhesive material has good comprehensive performance.

[0042] Furthermore, the molecular weight of the waste solidified microparticles is 15000-25000. When the molecular weight of the waste solidified microparticles is within the range of 15000-25000, the viscosity is more suitable, and the composite adhesive material formed after mixing with the polyvinyl acetate emulsion has better performance. The molecular weight of the above waste solidified microparticles is based on the degree of coating curing reaction and is usually a theoretical average value.

[0043] Furthermore, the stirring speed is 200-300 r / min, and the stirring time is 10-15 min. When the stirring speed and stirring time of the stirrer are controlled within the above range, the waste solidified microparticles can be evenly dispersed in the polyvinyl acetate emulsion.

[0044] In addition, the present invention also proposes a composite adhesive material, which is prepared by any of the above-mentioned methods for preparing composite adhesive materials. The composite adhesive material is prepared by any of the above-mentioned methods for preparing composite adhesive materials using waste solidified microparticles, that is, the composite adhesive material has the same beneficial effects as above, which will not be described one by one here.

[0045] Furthermore, at room temperature, the curing time of the composite adhesive material applied on the substrate is 1-2 hours, and the substrate includes one of the wood materials. After the composite adhesive material prepared in this scheme is applied on the substrate (wood material), the drying time at room temperature (25±5°C) is 1-2 hours.

[0046] The substrate of the present solution can be a wood material, a bamboo material or a resin material. It is particularly preferred that the composite adhesive material of the present solution is applied to the bonding of wood materials.

[0047] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0048] Comparative Example 1

[0049] By weight percentage, the existing polyvinyl acetate adhesive formula includes: 45% vinyl acetate, 5% polyvinyl alcohol, 4% dibutyl phthalate, 1% octanol, 0.1% ammonium persulfate, and 44.9% water.

[0050] Example 1

[0051] A method for preparing a composite adhesive material using waste solidified microparticles comprises the following preparation steps:

[0052] S1. Collect the waste solidified micro particles remaining after the UV coating on the door panel is polished through the central dust removal system;

[0053] S2. After the collected waste solidified microparticles are sieved, impurities are removed and set aside;

[0054] S3. Add the sieved waste solidified microparticles to the polyvinyl acetate emulsion and stir until evenly mixed to obtain a composite adhesive material.

[0055] This embodiment is divided into 6 groups according to the different addition amounts of waste solidified microparticles (other preparation steps are the same), see the following table:

[0056] Comparative Example 2

[0057] The preparation steps and parameters in this comparative example are the same as those in Examples 1-5, except that the polyvinyl acetate emulsion is replaced by polyvinyl formal.

[0058] The adhesive materials of Example 1 and Comparative Examples 1-2 were applied on the surface of the wood board to form a coating, and the properties of the coating and the adhesive materials were tested. The specific test results are shown in the following table:

[0059]

[0060] As shown in the test results in the table above, the composite adhesive materials obtained in Examples 1-2 to 1-5 all have good shear strength and stability, suitable viscosity and solid content, and moderate curing time; among them, the addition amount of waste solidified microparticles is preferably 12-14%, and the composite adhesive material obtained at this time has higher shear strength and can be stably present for 15 months. It can be seen from the test data of Example 1-1 that when the addition amount of waste solidified microparticles is too small, it is easy to cause the obtained composite adhesive material to be unqualified, and the composite adhesive material can be used stably for a short time.

[0061] It can be seen from the test results of Example 1 and Comparative Example 1 that directly using the existing polyvinyl acetate adhesive on the wood substrate (wooden board) will easily cause cracking of the adhesive layer after curing, and the existing polyvinyl acetate adhesive can be stable for a relatively short time. It can be seen from the test results of Example 1 and Comparative Example 2 that the waste solidified microparticles do not have good performance after being mixed with any type of adhesive, and the dry shear strength of the adhesive material obtained when the waste solidified microparticles are mixed with polyvinyl formal is low.

[0062] Example 2

[0063] The preparation steps and parameters in this embodiment are the same as those in Embodiments 1-5, except that the particle sizes of the waste solidified microparticles are different, as shown in the following table:

[0064]

[0065]

[0066] The composite adhesive material prepared in Example 2 was coated on the surface of the wood board to form a coating, and the properties of the coating and the composite adhesive material were tested. The specific test results are shown in the following table:

[0067]

[0068] As shown in the test data in the table above, from the test results of Examples 1-5 and 2, it can be seen that the particle size range of the waste solidified microparticles of this solution is preferably limited to below 250 μm. At this time, the composite adhesive material obtained has higher shear strength and better stability after long-term storage; it is preferred to use waste solidified microparticles of different particle sizes in combination, as shown in the test results of Examples 2-6, the shear strength of the composite adhesive material is further improved, and it also has better stability. When the particle size of the waste solidified microparticles is too large, as shown in Examples 2-4 to 2-5, the composite adhesive material obtained will also crack when applied to a wooden board.

[0069] Example 3

[0070] The preparation steps and parameters in this embodiment are the same as those in Embodiments 1-5, except that the viscosity and pH value of the polyvinyl acetate emulsion are different, as shown in the following table:

[0071]

[0072]

[0073] The composite adhesive material prepared in Example 3 was coated on the surface of the wood board to form a coating, and the properties of the coating and the composite adhesive material were tested. The specific test results are shown in the following table:

[0074]

[0075] As shown in the test data in the above table, it can be seen from the test results of Examples 1-5 and Example 3 that before mixing with the waste solidified microparticles, the viscosity of the polyvinyl acetate emulsion in this scheme is preferably 9000-11000m Pa·S, and the pH value is preferably 5-8. When controlled within the above range, the obtained composite adhesive material has better performance.

[0076] Example 4

[0077] The preparation steps and parameters in this embodiment are the same as those in Embodiments 1-5, except that the types of waste solidified microparticles are different, as shown in the following table:

[0078]

[0079] The composite adhesive material prepared in Example 4 was coated on the surface of the wood board to form a coating, and the properties of the coating and the composite adhesive material were tested. The specific test results are shown in the following table:

[0080]

[0081]

[0082] As shown in the test data in the above table, it can be seen from the test results of Examples 1-5 and Example 4 that the waste solidified microparticles are preferably a mixture of three types of waste solidified microparticles of epoxy resin, waste solidified microparticles of polyurethane resin and waste solidified microparticles of acrylic resin. In this case, the performance of the composite adhesive material obtained is improved.

[0083] Example 5

[0084] A method for preparing a composite adhesive material using waste solidified microparticles comprises the following preparation steps:

[0085] S1. Collect the waste solidified microparticles remaining after the UV coating on the door panel is polished through the central dust removal system, among which the waste solidified microparticles with a particle size of ≤50um account for 20%, the particle size of 50-100um accounts for 30%, and the particle size of 200-250um accounts for 50%. The waste solidified microparticles are formed by mixing waste solidified microparticles of epoxy resin, waste solidified microparticles of polyurethane resin, and waste solidified microparticles of acrylic resin (the mass ratio of the three is 2:1:2.5);

[0086] S2. After the collected waste solidified microparticles are sieved, impurities are removed and set aside;

[0087] S3. The sieved waste solidified microparticles were added to 88% polyvinyl acetate emulsion (viscosity of mPa·S, pH of 6) at a ratio of 12%, and stirred until evenly mixed to obtain a composite adhesive material.

[0088] The composite adhesive material prepared in Example 5 was coated on the surface of the wood board to form a coating, and the properties of the coating and the adhesive material were tested. The specific test results are shown in the following table:

[0089]

[0090] From the test results in the above table, it can be seen that by further optimizing the particle size of the waste solidified microparticles, the type of the waste solidified microparticles and the parameters of the polyvinyl acetate emulsion, the dry shear strength of the composite adhesive material can be increased to above 13 MPa, while also maintaining long-term storage stability.

[0091] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or direct / indirect application in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a composite adhesive material using waste solidified microparticles, characterized in that: The method comprises the following steps: mixing 8% to 20% of waste solidified microparticles with 80% to 92% of polyvinyl acetate emulsion by mass percentage, and stirring the mixture to obtain a composite adhesive material; The waste solidified micro-particles are waste particles remaining after the UV coating is polished.

2. The method for preparing a composite adhesive material using waste solidified microparticles according to claim 1, characterized in that: The waste solidified microparticles are first sieved before mixing, and the particle size of the waste solidified microparticles after sieving is ≤250 μm.

3. The method for preparing a composite adhesive material using waste solidified microparticles according to claim 1, characterized in that: The waste solidified microparticles include waste solidified microparticles of epoxy resin, waste solidified microparticles of polyurethane resin and waste solidified microparticles of acrylic resin.

4. The method for preparing a composite adhesive material using waste solidified microparticles according to claim 3, characterized in that: The mass ratio of the epoxy resin waste solidified microparticles, the polyurethane resin waste solidified microparticles and the acrylic resin waste solidified microparticles is 2:1:2.

5.

5. The method for preparing a composite adhesive material using waste solidified microparticles according to claim 1, characterized in that: 12%-14% of the waste solidified micro-particles and 86%-88% of the polyvinyl acetate emulsion are mixed by mass percentage and stirred evenly to obtain a composite adhesive material.

6. The method for preparing a composite adhesive material using waste solidified microparticles according to claim 1, characterized in that: The viscosity of the polyvinyl acetate emulsion is 9000-11000 mPa·S, and the pH value is 5-8.

7. The method for preparing a composite adhesive material using waste solidified microparticles according to claim 1, characterized in that: The molecular weight of the waste solidified microparticles is 15000-25000.

8. The method for preparing a composite adhesive material using waste solidified microparticles according to claim 1, characterized in that: The stirring speed during stirring is 200-300r / min, and the stirring time is 10-15min.

9. A composite adhesive material, characterized in that: The composite adhesive material is prepared by the method for preparing the composite adhesive material using waste solidified microparticles as described in any one of claims 1 to 8.

10. A composite adhesive material according to claim 9, characterized in that: Under room temperature conditions, the curing time of the composite adhesive material coated on the substrate is 1-2 hours, and the substrate includes a wood material.